Computational drug repurposing for tuberculosis by inhibiting Ag85 complex proteins - Iskandar, Israini W.; Nurhasanah, Astutiati; Hatta, Mohammad; Hamid, Firdaus; Handayani, Irda; Chaera, Ummi; Yusriyyah, Andi A.; Jamaluddin, Balqis D.; Zaenab, St; Hidayah, Najdah; Karimah, Nihayatul; Permana, Andi D.; Massi, Muhammad N. (Narra J, 2025)
Tuberculosis (TB) remains a significant and deadly infection among pulmonary diseases caused by Mycobacterium tuberculosis, a highly adaptive bacterium. The ability of M. tuberculosis to evade certain drugs has been linked to its unique structure, particularly in the cell envelope, where the Ag85 complex proteins play an essential role in this part.  The aim of this study was to utilize a drug repurposing strategy targeting the Ag85 complex proteins. This study utilized a computational approach with 120 selected drugs experimentally identified to inhibit Tuberculosis. A virtual screening molecular docking with Autodock Vina was used to filter the compounds and identify the strong binders to the Ag85 Complex. Molecular dynamics simulations employed the Gromacs Packages to evaluate the stability of each complex, including root mean square deviation (RMSD), root mean square fluctuation (RMSF), and radius of gyration (RoG). Additionally, absorption, distribution, metabolism, excretion, and toxicity (ADMET) assessments were conducted to gather more information about the drug-likeness of each hit compound. Three compounds, selamectin, imatinib, and eltrombopag were selected as potential drugs repurposed to inhibit the activity of the Ag85 complex enzyme, with binding affinities ranging between -10.560 kcal/mol and -11.422 kcal/mol. The MD simulation within 100 ns (3 replicas) showed that the average RMSD of each Ag85A complex was 0.15 nm–0.16 nm, RMSF was 0.09 nm–0.10 nm, and RoG was 1.80 nm–1.81 nm. For Ag85B, the average RMSD was 1.79 nm–1.80 nm, RMSF was 0.08 nm–0.09 nm, and RoG was 1.79 nm – 1.80 nm. Then, for Ag85C, the mean RMSD was 0.16 nm–0.18 nm, RMSF was 0.09, and RoG was 1.77 nm. The study highlights that these promising results demonstrate the potential of some repurposed drugs in combating the Ag85 complex.